2007
DOI: 10.1073/pnas.0701096104
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of neuroinflammation and Alzheimer's disease pathology by liver x receptors

Abstract: Alzheimer's disease (AD) is an age-dependent neurodegenerative disease that causes progressive cognitive impairment. The initiation and progression of AD has been linked to cholesterol metabolism and inflammation, processes that can be modulated by liver x receptors (LXRs). We show here that endogenous LXR signaling impacts the development of AD-related pathology. Genetic loss of either Lxr␣ or Lxr␤ in APP/PS1 transgenic mice results in increased amyloid plaque load. LXRs regulate basal and inducible expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
224
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 305 publications
(243 citation statements)
references
References 66 publications
14
224
1
Order By: Relevance
“…This result agrees with findings in the literature of the contribution of lipid metabolism through liver X receptors (LXR) to the initiation and progression of this disease 52, 53…”
Section: Discussionsupporting
confidence: 93%
“…This result agrees with findings in the literature of the contribution of lipid metabolism through liver X receptors (LXR) to the initiation and progression of this disease 52, 53…”
Section: Discussionsupporting
confidence: 93%
“…Inhibition of glial activation and reduction of glial-induced neurotoxicity by GW3965 appear to have prevented the loss of dopaminergic neurons in the PD mouse model. The present study is in line with a study by Zelcer et al (42) showing that an LXR agonist inhibits the inflammation response of primary glial cell and increases phagocytic capacity to fibrillar Aβ peptide in the setting of Alzheimer's disease in vitro.…”
Section: Discussionsupporting
confidence: 81%
“…They suggest that this is a mechanism for removal and redistribution of cholesterol, which would be of benefit in neurodegenerative diseases associated with cholesterol accumulation in neurons. Similarly, Zelcer et al (39) have suggested that LXRs may be targets in treatment of Alzheimer's disease because of their ability to modulate both lipid metabolism and inflammatory gene expression.…”
Section: Discussionmentioning
confidence: 99%